2007
DOI: 10.1175/jam2528.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Continuous Soil Moisture Simulations Using Different Soil Hydraulic Parameterizations for a Site in Germany

Abstract: Continuous time series of soil water content over a period of more than 9 months for a midlatitude sandy loam soil covered by grass are calculated with the Campbell and the van Genuchten soil hydraulic functions and the Clapp-Hornberger, Cosby et al., and Rawls-Brakensiek parameter sets. The results are compared with soil water content observed at several soil depths, and the water balance components are evaluated. The Campbell soil hydraulic functions are often used by meteorologists, whereas the van Genuchte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Instead, the atmospheric forcing is provided by measured time series of the relevant atmospheric data. Testing the performance of LSMs at the plot scale and driven by experimental climate data is a common practice, because the data needed for model evaluation can be gathered with relatively high accuracy and in high‐temporal resolution [ Dirmeyer et al ., ; Schädler , ; Mahecha et al ., ; Ingwersen et al ., ]. Simulation results are compared with eddy covariance (EC) measurements of turbulent fluxes of water and energy, measurements of ground heat flux, and time series of soil moisture at different depths.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the atmospheric forcing is provided by measured time series of the relevant atmospheric data. Testing the performance of LSMs at the plot scale and driven by experimental climate data is a common practice, because the data needed for model evaluation can be gathered with relatively high accuracy and in high‐temporal resolution [ Dirmeyer et al ., ; Schädler , ; Mahecha et al ., ; Ingwersen et al ., ]. Simulation results are compared with eddy covariance (EC) measurements of turbulent fluxes of water and energy, measurements of ground heat flux, and time series of soil moisture at different depths.…”
Section: Introductionmentioning
confidence: 99%
“…In der Klimafolgenforschung und für verschiedene Anwendungen setzt man zudem statistische oder statistisch-dynamische Regionalisierungen globaler Modelle ein (Enke et al 2005;Spekat et al 2007Spekat et al , 2010Kreienkamp et al 2011aKreienkamp et al , 2013. (Heise et al 2003), VEG3D (Schädler 2007), CLM2 (Davin et al 2011;Edouard et al 2011) und REMO-iMOVE (Reick et al 2013;Wilhelm et al 2014).…”
Section: Methoden Der Regionalen Klimamodellierungunclassified
“…For this reason, our first step in parameterizing the M&M model was to find an initial set of parameter values that could reasonably reproduce infiltration rates and water content profiles similar to the solution of the Richards equation. Many studies (Schädler, 2007 for example) have demonstrated that the Richards equation can be used with various pedotransfer functions to reasonably represent moisture redistribution in soils, even though these equations sometimes cannot simulate ponded infiltration with the same parameter set. Therefore these Richards equation solutions were used to simulate infiltration for a range of soil types to obtain consistent initial estimates of parameters for the M&M infiltration model as a starting point for understanding how various parameters affect water movement.…”
Section: Initial Parameterization: Methodsmentioning
confidence: 99%